Analyzing Physical Education Teachers' Humour Styles and Classroom Management Skills - Hakan Sunay; Recep Cengiz (ümit doğan üstün, 2020)
This study aimed to examine the differences in the perception of humor styles and classroom management skills of PE teachers according to age, gender and seniority. Data related to PE teachers' humor styles were collected through Humor Styles Questionnaire developed by Martin et al. (2003), and adapted to Turkish by Yerlikaya in 2003, while data regarding classroom management skills were obtained via "Classroom Management Skills Scale" initially developed by Denkdemir in 2007. The study sample was composed of 162 physical education teachers employed in secondary and high schools in Bartın province. In the analyzes of the data One Way ANOVA, Tukey's HSD and independent samples t-test were used. According to analyze results, there were significant differences in the self-enhancing humor sub-dimension and classroom management skills according to age. Besides, there were significant differences in the classroom management skills according to gender and seniority, and humor styles of the teachers significantly differed in the affiliative humor sub-dimension, according to seniority. In conclusion, this paper demonstrated original and interesting results on associations in PE teachers humor styles and classroom management skills. However, further research is still recommended.